2019
DOI: 10.1016/j.maturitas.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

EMAS position statement: Predictors of premature and early natural menopause

Abstract: Introduction: While the associations of genetic, reproductive and environmental factors with the timing of natural menopause have been extensively investigated, few epidemiological studies have specifically examined their association with premature (< 40 years) or early natural menopause (40-45 years). Aim: The aim of this position statement is to provide evidence on the predictors of premature and early natural menopause, as well as recommendations for the management of premature and early menopause and futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
3
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 83 publications
4
77
3
18
Order By: Relevance
“…The results of this study suggest that the natural age of menopause in Chinese women is 49.49 ± 3.67 years old, and factors that may affect the age of natural menopause include body weight, age of menarche, marital status, frequent tea drinking, dietary supplements, oral contraceptive use, and safe period contraception methods. Our research showed that weight may be related to the age of menopause, which is consistent with the report by other papers [21][22][23][24]. The age of menarche was signi cantly related to the age of menopause, similar to previous research in Norwegian women [25].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of this study suggest that the natural age of menopause in Chinese women is 49.49 ± 3.67 years old, and factors that may affect the age of natural menopause include body weight, age of menarche, marital status, frequent tea drinking, dietary supplements, oral contraceptive use, and safe period contraception methods. Our research showed that weight may be related to the age of menopause, which is consistent with the report by other papers [21][22][23][24]. The age of menarche was signi cantly related to the age of menopause, similar to previous research in Norwegian women [25].…”
Section: Discussionsupporting
confidence: 93%
“…Unexhausted follicles can continue to mature, secrete estrogen, and expel the ovum. Marital status, frequent tea drinking, dietary supplements, oral contraceptive, and safe period contraception were related to the age of menopause, which are also consistent with current reports [21][22][23][24][26][27][28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, OTCT may be not successful or may no longer be possible because of deterioration of the primary cancer and/or development of metastases, and these patients will develop POI with all its negative consequences. The prevalence of POI is as high as 7% in UK, which may be higher than 10% in China, of which 20-56% are caused by iatrogenic factors, and radiotherapy and/or chemotherapy can cause POI in 70-100% of women [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%